Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1177/1934578x0800301117
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Variation in the Diterpenes from the Brazilian Brown Alga Dictyota Menstrualis (Dictyotaceae, Phaeophyceae)

Abstract: All the chemical HRGC/MS profiles of samples of Dictyota menstrualis, collected in Buzios, Rio de Janeiro and São Pedro and São Paulo Archipelago, Brazil, presented diterpenes as major constituents. The samples contained either prenylated guaiane or xeniane derivatives as their major diterpenes. However, there was a variation concerning the quantity of these components. Taking this into consideration, it is possible to establish typical geographic patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…Ortiz‐Ramirez et al. () showed spatial variation with the quantity of diterpenes in Dictyota menstrualis , which enabled typical geographic patterns to be established for this species. Moreover, Fleury et al.…”
Section: Discussionmentioning
confidence: 99%
“…Ortiz‐Ramirez et al. () showed spatial variation with the quantity of diterpenes in Dictyota menstrualis , which enabled typical geographic patterns to be established for this species. Moreover, Fleury et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is worthwhile to mention that the polarity of solvents may also influence the potency of some pharmacological effects, since different molecules can be extracted [40]. The extracts evaluated in this work contain nonpolar molecules, such as diterpenes, fatty acids or sterols.…”
Section: Resultsmentioning
confidence: 99%
“…The male and female gametophytes and the sporophyte are identical in appearance. In our previous studies conducted along the Brazilian littoral, it was observed in the field that different haploid-diploid ratios of the alternating life stages of D. menstrualis can be found at the same time in the field throughout the year (Cavalcanti et al 2006;Ortiz-Ramirez et al 2008;Pereira et al 2000;Teixeira et al 2001).…”
Section: Introductionmentioning
confidence: 97%